2013
DOI: 10.4028/www.scientific.net/amr.832.113
|View full text |Cite
|
Sign up to set email alerts
|

Plant Diseases Detection Using Nanowire as Biosensor Transducer

Abstract: The plant disease such as Cucumber Mosaic Virus (CMV) and Papaya Ring Spot Virus (PRSV) is a most dangerous disease that can decrease productivity and quality of the vegetable and fruit. Besides that, its also can destroy and kill those plant in long term when infected and to tackle this problem at early stages, the nanowire based biosensor application is a most reliable sensor nowadays because of advantages towards detecting biological molecule especially plant diseases.In order to dealing with tiny form of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 3 publications
(2 reference statements)
0
7
0
Order By: Relevance
“…New revolutionary technologies in nucleic acid molecular imaging and sequencing have enabled advances in plant research [ 133 ]. Conventional mass spectroscopy can accurately identify cellular and subcellular localization and metabolite levels using critical data on the dynamics and location of enzymes, although transporters, substrates, and receptors still need advancement.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…New revolutionary technologies in nucleic acid molecular imaging and sequencing have enabled advances in plant research [ 133 ]. Conventional mass spectroscopy can accurately identify cellular and subcellular localization and metabolite levels using critical data on the dynamics and location of enzymes, although transporters, substrates, and receptors still need advancement.…”
Section: Applicationsmentioning
confidence: 99%
“…Biosensors can access these data to quantify an active process under physiological circumstances. Strategies to envision actual processes, such as changing one metabolite into another or generating signal events, have also been attempted [ 133 ]. Tsien [ 134 ] was the first to produce protein prototype sensors for detecting caspase activity and calcium levels in living cells.…”
Section: Applicationsmentioning
confidence: 99%
“…In another approach, portable equipment was used to detect bacterial, fungal species in stored food grains. Likewise, Ariffin et al [ 22 ] formulated a nanowire biosensor to detect Cauliflower Mosaic Virus and Papaya Ring Spot Virus. Thus, with the above scientific evidence, it can be identified that nano-based sensors and kits play a vital role in crop health care including products for rapid testing, disease diagnostics, and environmental monitoring aspects.…”
Section: Nanotechnology Advances For Improved Pathogen Diagnosismentioning
confidence: 99%
“…13 Now a day's nano-based materials is introduced which enhance the effectiveness of fungicides and pesticides, enabling minor dosages to be utilized. 14 Additionally, nanodiagnostic and microfluidics offer novel tools to improve the sample preparation step that remains difficult to incorporate in a miniaturized platform. The signal intensification methodologies may perhaps challenge those of target enhancement.…”
Section: Biosensor Based Diagnosismentioning
confidence: 99%